Development Audiovisual Health Education Media for Self Management of Hypertension Patients - Larasati Dyah Pertiwi; Shobirun Shobirun; Nina Indriyawati (Media Karya Kesehatan, 2021)
Complications of hypertension disease can be prevented by health promotion through the health education of hypertension self-management by using audiovisual media adapted to the development of information technology. However, hipertensive self management audiovisual is still very rarely found and used. This research aims to develop audiovisual health educational media for self management of hypertensive patients. This research used R&D (Research and Development) method with ADDIE model. The subject of this study was 3 experts for validation testing and 10 random respondents for a limited trial to determine product eligibility. The analysis of the data used the quantitative descriptive data by calculating the presentation of the media assessment score and qualitative descriptive data by recapitulating suggestions and comments for media revision. The resulting media was a video with a duration of 11 minutes and 28 seconds. The result of study that validated by experts was 80% (proper category) in material aspect, 78.3% (feasible category) in the content aspect and 89.2% (decent category) in display aspect. From the pilot study on 10 respondents found that display aspect was 95.4%, the content of material aspect was 93.5% and the understanding aspect was 95% with the very feasible category. The results showed that the audiovisual media about self-management for hypertension patients got a decent category as a media for health education. This media can be used for health education in hypertension patients but need for further research to test the media in proper hypertension groups.Keywords: Audiovisual, Health Education, Hypertension, Media Development, Self-management